2002
DOI: 10.1115/1.1459076
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Rotating Stall in a Pump Vaned Diffuser

Abstract: This paper treats the flow instabilities in a vaned diffuser by using CFD. A commercial code with the standard κ-ε turbulence model was used for the present work. It was found that the flow instabilities in the vaned diffuser: i.e., rotating stall, alternate blade stall, and asymmetric stall, could be simulated by the present calculations. These instabilities were observed in a range with negative slope of the pressure performance curve of the diffuser. The rotating stall onset flow rate is larger for the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 5 publications
2
33
0
Order By: Relevance
“…Their results compared with PIV results obtained in a previous experimental analysis [16] had better predicted the flow field evolution than the most common turbulence models of those years (k-ε and Baldwin-Lomax turbulence models). Another numerical analysis was presented by Sano et al [17], demonstrating the development of a rotating stall which causes in the diffuser channels the switching between reverse and jet flows, in good agreement with experimental results.…”
Section: Introductionsupporting
confidence: 58%
“…Their results compared with PIV results obtained in a previous experimental analysis [16] had better predicted the flow field evolution than the most common turbulence models of those years (k-ε and Baldwin-Lomax turbulence models). Another numerical analysis was presented by Sano et al [17], demonstrating the development of a rotating stall which causes in the diffuser channels the switching between reverse and jet flows, in good agreement with experimental results.…”
Section: Introductionsupporting
confidence: 58%
“…Many researches have been carried out to investigate unsteady flow in centrifugal pump. At off-design conditions, separate flow would develop on blade suction side leading to partial impeller channels being blocked [9]. At low flow rates, especially, the separate flow structure may transfer from one blade channel to the adjacent channel forming rotating stall phenomenon [10].…”
Section: Introductionmentioning
confidence: 99%
“…Niazi et al performed the three-dimensional numerical simulation of a high-speed transonic fan rotor considering external disturbance, and the results showed that the reflux first occurred near the blade leading-edge in the rotor tip clearance area [2]. Sano et al conducted detailed research on the unsteady flow phenomena inside the pump vaned diffuser, such as the rotating stall, the alternate blade stall, and the asymmetric stall [3]. Shen et al presented a three-dimensional model to study the occurrence of weak rotating waves in vaneless diffusers of centrifugal compressors, and the results showed that the critical flow angle and the stall propagation velocity were affected by the axial distributions of undisturbed flow at the diffuser inlet [4].…”
Section: Introductionmentioning
confidence: 99%